2015
DOI: 10.1590/1678-457x.6715
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of frozen tortillas from nixtamalized maize flours enriched with β-glucans

Abstract: Effects of different β-glucan concentrations in maize flour on the properties of frozen maize tortillas were evaluated. Masa (dough), pre-cooked (PTs), frozen (FTs), thawed (TTs), and cooked tortillas (CTs) were made and analyzed. Moisture content of masa and tortillas significantly decreased as β-glucan concentration increased; however, the water absorption capacity (WAC), ice melting enthalpy, and frozen water in FTs increased. Texture and color of the masa, PTs, and CTs as well as sensory analysis showed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(62 reference statements)
0
4
0
2
Order By: Relevance
“…BG has various functional properties that can be utilized in food industries for the preparation of soups, sauces, beverages, and other food products where BG act as stabilizing, thickening agents, and emulsifier (Dawkins & Nnanna, 1995;Burkus & Temelli, 2000;Sánchez-Madrigal et al, 2015). BG is also known for several beneficial effects on various diseases and disorders such as colorectal cancer (Dongowski et al, 2002), prevention of coronary heart disease (Wang et al, 2002), blood glucose levels and insulin resistance (Hallfrisch et al, 2003;Hlebowicz et al, 2008), serum cholesterol levels, and gut microflora (Tungland, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…BG has various functional properties that can be utilized in food industries for the preparation of soups, sauces, beverages, and other food products where BG act as stabilizing, thickening agents, and emulsifier (Dawkins & Nnanna, 1995;Burkus & Temelli, 2000;Sánchez-Madrigal et al, 2015). BG is also known for several beneficial effects on various diseases and disorders such as colorectal cancer (Dongowski et al, 2002), prevention of coronary heart disease (Wang et al, 2002), blood glucose levels and insulin resistance (Hallfrisch et al, 2003;Hlebowicz et al, 2008), serum cholesterol levels, and gut microflora (Tungland, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Colour values found in this study are similar to those reported by Sánchez‐Madrigal et al . () for laboratory made tortillas. Colour of tortilla is an extremely important characteristic of visual quality.…”
Section: Resultsmentioning
confidence: 99%
“…Durante los procesos de investigación la intervención de las instituciones u organizaciones juegan un papel fundamental en la ejecución y divulgación del conocimiento, en consecuencia la Figura 2 muestra las 15 instituciones con mayor participación en relación al mayor número de publicaciones sobre el tema de búsqueda, fueron: Texas A&M University (Seetharaman et al, 2002;Mondal et al, 2008;Santana-Gálvez et al, 2016), Jiangnan University (Zhou et al, 2016;Sharif et al, 2017;Yue et al, 2017), National Technical University of Athens (Sabanis et al, 2009;Lebesi & Tzia, 2011;Sabanis & Tzia, 2011), Iowa State University (Seetharaman et al, 2002;Vidal-Quintanar et al, 2003;Antunez et al, 2012) y Sonora University (Vidal-Quintanar et al, 2003;Márquez-Castillo & Vidal-Quintanar, 2011;Sánchez-Madrigal et al, 2015); resaltando las dos primeras instituciones como aquellas que presentaron publicaciones en los últimos dos años, de igual manera sobresale la participación de CSIR, University Minnesota, University of Johannesburg, Brigham Young University y University Auckland con publicaciones en el año 2017. Cuando ocurre una interacción entre una o más instituciones se convierte en un pilar para el intercambio y multidisciplinariedad del conocimiento científico como ocurre entre Texas A&M University y Iowa State University que generan conocimiento acerca las propiedades de textura, viscosidad y térmicas de dos productos horneados comunes hechos de harina de trigo, panecillos y tortillas de maíz (Seetharaman et al, 2002); y también la interacción que presenta esta última institución con Sonora University en contribuir con la información en temas de vida útil en masa de maíz nixtamalizadas con procesos de autooxidación (Vidal-Quintanar et al, 2003).…”
Section: Institucionesunclassified
“…De los autores más citados encontramos a Arendt EK con 2 publicaciones y un total de 128 citaciones (Moroni et al, 2009;Zannini et al, 2012) y de la contribución de autores por documento se encontró que de todos los documentos solo uno contaba con la participación de 9 autores (Sharif et al, 2017) y 3 documentos con la participación de 8 autores cada una (Okeke et al, 2015;Sánchez-Madrigal et al, 2015;Valderrama-Bravo et al, 2017). Seetharaman et al (2002), Mondal et al (2008) Catzeddu P 2 Italia 2 6 Sanguinetti et al (2015), Sanguinetti et al (2016) Giannuzzi L 2 Argentina 1 3 Oteiza et al (2003), Gamba et al (2016)…”
Section: Indicadores De Visibilidadunclassified